2015
DOI: 10.2174/1568026615666150825125857
|View full text |Cite
|
Sign up to set email alerts
|

Histone and Non-Histone Targets of Dietary Deacetylase Inhibitors

Abstract: Acetylation is an important, reversible post-translational modification affecting histone and non-histone proteins with critical roles in gene transcription, DNA replication, DNA repair, and cell cycle progression. Key regulatory enzymes include histone deacetylase (HDACs) and histone acetyltransferases (HATs). Overexpressed HDACs have been identified in many human cancers, resulting in repressed chromatin states that interfere with vital tumor suppressor functions. Inhibition of HDAC activity has been pursued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 217 publications
2
52
0
Order By: Relevance
“…HDACi, and other compounds, derived from plants, herbs, and foods stuffs are known to be bioactive compounds [15]. Bioactive HDACi as well as their descriptions and specifications can be found in some detail [49,50]. Cyclic peptide and shortchain fatty acid HDACi are the more familiar types of bioactive HDACi.…”
Section: Bioactive Hdacimentioning
confidence: 99%
See 4 more Smart Citations
“…HDACi, and other compounds, derived from plants, herbs, and foods stuffs are known to be bioactive compounds [15]. Bioactive HDACi as well as their descriptions and specifications can be found in some detail [49,50]. Cyclic peptide and shortchain fatty acid HDACi are the more familiar types of bioactive HDACi.…”
Section: Bioactive Hdacimentioning
confidence: 99%
“…Other bioactive compounds from foods have been identified that regulate HDAC activity, including curcumin and resveratrol [50,52,53]. Resveratrol has been shown to regulate Sirtuins and has been extensively reviewed.…”
Section: Bioactive Hdacimentioning
confidence: 99%
See 3 more Smart Citations